New method for the geometric design of the runner wheel of the Bánki turbine - Hajdú, Sándor (Design of Machines and Structures, 2023)
This article is a continuation of a previous publication by Author. Paper (Hajdú, 2022) analyses the velocity relationships in the flow stream through the Bánki turbine. By exploring the velocity relationships, it is possible to determine the flow losses in the turbine runner and the runner efficiency of the runner. By implementing the theoretical results in practice, a new design procedure for the geometry of the runner of the Bánki turbine is developed.